Use of native microalgae in anaerobic sewage treatment: Lab and pilot-scale approaches - Pompei, Caroline Moço Erba [UNESP]; Bolzani, Hugo Renan [UNESP]; da Silva, Gustavo Henrique Ribeiro [UNESP] (Springer Nature, 2023)
Microalgae-based systems have the potential to remove the nutrients from the sewage that can be reused for agricultural purposes for example. However, there are very few pilot-scale studies conducted in tropical regions. In this study, real anaerobically digested sewage was treated using a native microalgae consortium as inoculum in a lab-scale flat panel photobioreactor operated indoor and a pilot scale flat panel operated outdoors under tropical conditions. The performance was then evaluated by assessing the nutrient removal efficiency and biomass productivity. Both, the indoor and the outdoor photobioreactors were operated in batch mode (seven days each) in southeastern Brazil. This study showed that both bioreactors operated under tropical climatic conditions had a positive performance, however the outdoor flat panel had better performance in terms of nutrient removal (average removals of 85% total nitrogen and 88% total phosphorus) and biomass productivity in terms of total suspended solids (average of 31.3 mg L−1 day−1), mainly because of better light and temperature. Tetradesmus sp. and Mychonastes homosphaera were dominant during the study period in both, indoor and outdoor photobioreactors.
Keywords: Biomass productivity; Irradiance; Nutrient removal; Phycoremediation; Removal rate